Methylglyoxal Accumulation in Arterial Walls Causes Vascular Contractile Dysfunction in Spontaneously Hypertensive Rats - Masashi Mukohda; Muneyoshi Okada; Yukio Hara; Hideyuki Yamawaki (Elsevier, 2012)
Methylglyoxal (MGO) is a metabolite of glucose and perhaps mediates diabetes-related macrovascular complications including hypertension. In the present study, we examined if MGO accumulation affects vascular reactivity of isolated mesenteric artery from spontaneously hypertensive rats (SHR). Five-week-old SHR were treated with an MGO scavenger, aminoguanidine (AG), for 5 weeks. AG partially normalized increased blood pressure in SHR. In mesenteric artery from SHR treated with AG, increased accumulation of MGO-derived advanced glycation end-products was reversed. In mesenteric artery from SHR, AG normalized impaired acetylcholine (ACh)-induced relaxation and increased angiotensin (Ang) II-induced contraction. Reactive oxygen species (ROS) production increased in SHR mesenteric artery, and acute treatment with a nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) inhibitor augmented ACh-induced relaxation. Protein expression of NOX1 and Ang II type 2 receptor (AT2R) increased in SHR mesenteric artery, which was normalized by AG. Acute treatment with an AT2R blocker but not a NOX inhibitor normalized the increased Ang II-induced contraction in SHR mesenteric artery. The present results demonstrate that MGO accumulation in mesenteric artery may mediate development of hypertension in SHR at least in part via increased ROS-mediated impairment of endothelium-dependent relaxation and AT2R-mediated increased Ang II contraction. Keywords:: glucose metabolite, smooth muscle, endothelium, vascular reactivity, reactive oxygen species